The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1469-1809.2007.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation Analysis of the Phenylalanine Hydroxylase (PAH) Gene in the Israeli Population

Abstract: SummaryHyperphenylalaninemia (HPA) is a group of diseases characterized by a persistent elevation of phenylalanine levels in tissues and biological fluids. The most frequent form is phenylalanine hydroxylase deficiency, causing phenylketonuria (PKU). Among 159 Israeli patients (Jews, Muslim and Christian Arabs and Druze) with HPA, in whom at least one of the mutations was characterized, a total of 43 different mutations were detected, including seven novel ones. PKU was very rare among Ashkenazi Jews and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…This loss of enzymatic function is most likely caused by conformational changes due to the presence of three additional amino acids (Gly-Leu-Gln) between the normal sequences encoded by exon 10 and exon 11 (Dworniczak et al, 1991). This mutation has been identified as the most common mutation in Mediterranean populations such as Turkey (Dobrowolski et al, 2011), Italy (Daniele et al, N. Ajami et al 2007), Spain (Desviat et al, 1999), Egypt (Effat et al, 1999), and Israel (Bercovich et al, 2008). In previous studies that have been performed in Iran, IVS10-11G>A was also identified with the highest frequency (Bonyadi et al, 2010;Zare-Karizi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This loss of enzymatic function is most likely caused by conformational changes due to the presence of three additional amino acids (Gly-Leu-Gln) between the normal sequences encoded by exon 10 and exon 11 (Dworniczak et al, 1991). This mutation has been identified as the most common mutation in Mediterranean populations such as Turkey (Dobrowolski et al, 2011), Italy (Daniele et al, N. Ajami et al 2007), Spain (Desviat et al, 1999), Egypt (Effat et al, 1999), and Israel (Bercovich et al, 2008). In previous studies that have been performed in Iran, IVS10-11G>A was also identified with the highest frequency (Bonyadi et al, 2010;Zare-Karizi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another genetic recessive disease prevalent among Jews of Yemenite extraction is Phenylketonuria. It is estimated to affect 1: 5,000 live births in Jews of Yemenite extraction [21] . All affected subjects have the same molecular defect, a deletion spanning the third exon of the phenylalanine hydroxylase gene [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Each monomer has three structural domains: an N-terminal regulatory domain (residues 1-142), a catalytic domain (residues 143-410), and a C-terminal tetramerization domain (residues 411-452). The studies have provided information on the active site and binding sites for its substrate and cofactor [2].…”
Section: Introductionmentioning
confidence: 99%